Understanding adult attachment in family relationships : research, assessment and intervention - Bifulco, Antonia, 1955- (Routledge, 2013)
"This practical book introduces and explains an easily accessible assessment tool for adult attachment style, the Attachment Style Interview (ASI). Based on extensive research study, it discusses appropriate interventions and case assessments that can be made to help families in need. Simpler than the Adult Attachment Interview, which requires expert administration, the ASI is an invaluable and evidence-based resource and is particularly useful for multi-agency practitioners working with children and families, including those in adoption and fostering, child safeguarding and therapeutic services. Presenting clear and concise descriptions of the measure and summaries of the attachment models developed, it provides discussions of its relevance for different practice contexts. This text uses a range of worked case studies to illustrate its principles and applications. It details attachment issues in different relationship domains to cover areas of risk and resilience relevant for practice such as: adult depression and anxiety and stress models, partner difficulties including domestic violence, childhood neglect and abuse as a source of attachment problems, parenting and intergenerational transmission of risk, resilience factors, interventions, service application and use in family therapy. Understanding Adult Attachment in Family Relationships provides an important reference for all practitioners working with children, adolescents and families, especially those undertaking further study"--Provided by publisher.